Brand activation strategy of @kebulsate.jogja through Instagram as a social media platform in building brand image (BIS Humanities and Social Science, 2026)
Social media has become a strategic platform for micro, small, and medium enterprises (MSMEs) to build brand image effectively and affordably. This study aims to analyze the brand activation strategy implemented by @kebulsate.jogja through Instagram and its contribution to brand image formation. The research employs a descriptive qualitative approach using in-depth interviews, Instagram content documentation, and source triangulation, while data analysis is conducted through data reduction, data display, and thematic conclusion drawing based on the brand activation framework. The findings reveal that the strategy is implemented systematically through five stages: discovery, strategic development, creative development, delivery, and evaluation. Its implementation is reflected in informative content highlighting the uniqueness of herbal red seasoning, the use of customer testimonials as social proof, and cross-MSME collaborations to expand reach and strengthen positioning. Conceptually, these practices function not only as promotional activities but also as mechanisms for building brand association, emotional engagement, and relational bonding that contribute to brand image formation.